1998
DOI: 10.1111/j.1740-8261.1998.tb00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐field Magnetic Resonance Imaging of Early Subchondral Cyst‐like Lesions in Induced Cranial Cruciate Ligament Deficient Dogs

Abstract: Six healthy adult male mongrel dogs underwent cranial cruciate ligament transection in the left stifle. Survey radiography of both stifles and low-field (0.064 T) MRI of the left stifle were performed preoperatively and at 2, 6, and 12 weeks postoperatively. Focal changes in signal intensity were seen with MRI in the subchondral bone of the medial tibial condyle at 2 and 6 weeks postoperatively. At 12 weeks postoperative, a cyst-like lesion was detected using MRI in the subchondral bone of the medial tibial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 23 publications
3
35
1
3
Order By: Relevance
“…Barrett et al (2009), with high-field MRI, used proton density-weighted (PD-weighted) images in the sagittal plane to evaluate cranial cruciate ligament abnormalities with a sensitivity of 0.93. In addition, in order to improve visibility oblique scans were performed that were aligned to the cranial cruciate ligament regardless of the strength of the magnetic field (Baird et al 1998a, Barrett et al 2009). Other authors used T2-weighted fast spin echo (FSE) sequence due to the difference in signal intensity between the cranial cruciate ligament and synovial fluid.…”
Section: Ligamentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Barrett et al (2009), with high-field MRI, used proton density-weighted (PD-weighted) images in the sagittal plane to evaluate cranial cruciate ligament abnormalities with a sensitivity of 0.93. In addition, in order to improve visibility oblique scans were performed that were aligned to the cranial cruciate ligament regardless of the strength of the magnetic field (Baird et al 1998a, Barrett et al 2009). Other authors used T2-weighted fast spin echo (FSE) sequence due to the difference in signal intensity between the cranial cruciate ligament and synovial fluid.…”
Section: Ligamentsmentioning
confidence: 99%
“…The study conducted by Baird et al (1998a) demonstrated that using low-field MRI they could visualize focal changes and cyst-like lesions in the subchondral bone in one of six dogs 2 weeks after cranial cruciate ligament insufficiency and in all the subjects investigated after 12 weeks. The changes were round with low signal intensity on T1-weighted images.…”
Section: Bonesmentioning
confidence: 99%
See 3 more Smart Citations